Acute Unilateral Central Serous Chorioretinopathy after Immunization with Pfizer-BioNTech COVID-19 Vaccine: A Case Report and Literature Review. (18th August 2022) - Rama Raj, Palaniraj; Adler, Paul A; Chalasani, Rajeev; Wan, Sue Ling
ABSTRACT: Introduction: A 43-year-old Caucasian male presented to our ophthalmology clinic with blurry vision and metamorphopsia in his right eye, 24 hours after receiving the first dose of the Pfizer–BioNTech COVID-19 vaccine. Methods: Clinical examination and imaging tests were consistent with acute unilateral central serous chorioretinopathy (CSCR) that completely resolved after 2 months without any treatment. He had no significant ophthalmic or medical history. He also lacked the classical risk factors for CSCR such as recent psychosocial stressors, Type-A personality traits, history of exogenous steroid use, connective tissue disorders and obstructive sleep apnea. Results: This appears to be only the second reported case of CSCR, temporally associated with a recombinant COVID-19 mRNA vaccine. We also present a summary of published reports demonstrating intraocular complications associated with the novel recombinant COVID-19 mRNA vaccines. Conclusion: Findings in this report should not deter COVID-19 vaccinations given the rarity of aforementioned ocular complications and the greater benefit of protection from COVID-19 infection. Medical practitioners, however, should remain mindful of potential ocular complications, given the greater likelihood of occurrence with increasing vaccination booster rates.